The Reality of Neandertal Symbolic Behavior at the Grotte du Renne, Arcy-sur-Cure, France - Caron, François; d'Errico, Francesco; Del Moral, Pierre; Santos, Frédéric; Zilhão, João (PLOS ONE, 2011)
Background The question of whether symbolically mediated behavior is exclusive to modern humans or shared with anatomically archaic populations such as the Neandertals is hotly debated. At the Grotte du Renne, Arcy-sur-Cure, France, the Châtelperronian levels contain Neandertal remains and large numbers of personal ornaments, decorated bone tools and colorants, but it has been suggested that this association reflects intrusion of the symbolic artifacts from the overlying Protoaurignacian and/or of the Neandertal remains from the underlying Mousterian. Methodology/Principal Findings We tested these hypotheses against the horizontal and vertical distributions of the various categories of diagnostic finds and statistically assessed the probability that the Châtelperronian levels are of mixed composition. Our results reject that the associations result from large or small scale, localized or generalized post-depositional displacement, and they imply that incomplete sample decontamination is the parsimonious explanation for the stratigraphic anomalies seen in the radiocarbon dating of the sequence. Conclusions/Significance The symbolic artifacts in the Châtelperronian of the Grotte du Renne are indeed Neandertal material culture.